Association Between MRI Findings of Facet Arthropathy and Synovitis With Health-Related Outcome and Pain Scores Following Therapeutic Lumbar Facet Injections - Michael S. Green; Michele Van Hal; Matthew Onimus; Christopher R. Hoffman; Dhruv K. C. Goyal; Valeria Potigailo; Khuram S. Kazmi (Anesthesiology Research and Practice)
Low back pain is a common complaint among adults. The facet joint is a major source of lumbar pain, and therapeutic facet injections have gained popularity as a minimally invasive treatment option. In addition, magnetic resonance imaging (MRI) utilization for diagnosing low back pain has increased significantly over the past few decades. Facet synovitis is an entity characterized by edema and inflammatory changes affecting the facet joints, adjacent bone marrow, and surrounding soft tissues. Although its underlying etiology remains poorly understood, recent reports suggest a high incidence in patients with arthropathy and arthritis. It is essential to explore potential correlations between specific MRI findings and outcomes after lumbar facet injections. This investigation is particularly relevant for facet synovitis, given its inflammatory nature and the common use of anti-inflammatory agents in facet injections. We investigated associations between MRI evidence of facet arthropathy and/or synovitis and the degree of improvement in health-related outcome and pain scores after therapeutic facet injections. The review was conducted on patients who received bilateral therapeutic facet injections, excluding those with prior lumbar spinal surgery or transitional segments. Facet arthropathy and synovitis were assessed on MRI by two neuroradiologists, and postprocedure outcomes such as pain and function were compared using univariate and multivariate analyses based on MRI findings. Our retrospective review indicates that patients receiving facet injections experience greater mean reduction in daily activity and workability burden scores from back pain when facet synovitis is a known portion of their pathology. The authors pose that further study could help identify patient populations that are the best candidates for therapeutic intervention. This may ultimately improve delivery of care, cost efficacy, and patient satisfaction.